High-concentration salt poly-zwitterionic gel electrolyte, zinc ion battery and preparation method
By using high-concentrated salt polyzwitterion gel electrolyte in zinc ion batteries, the synergistic effect of high-concentration zinc salt and polyzwitterion networks is used to solve the problems of leakage liquid, growth of zinc dendrites and decreased conductivity in zinc ion batteries, and the efficient ion conduction and long life of the battery are achieved.
Patent Information
- Application Number
- CN202411807399.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The aqueous electrolytes of existing zinc ion batteries are prone to leakage and zinc dendrites growth problems, and high concentration of zinc salt additives will increase the cost of the electrolyte and reduce ion conduction performance.
High-concentrated salt polyzwitterion gel electrolyte is used to form a three-dimensional network structure of zwitterionic copolymers through copolymerization, and the synergistic effect of high-concentration zinc salt and polyzwitterionic network is used to improve the ion conduction performance of the electrolyte.
It effectively inhibits the growth of zinc dendrites, extends the cycle life of the battery, and improves the conductivity, solves the problem of electrolyte leakage and ion conductivity degradation, and achieves excellent performance in safety performance, service life and electrical performance.
Smart Images

Figure CN119674276A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zinc ion batteries, in particular to a zinc ion battery using a polyamphoteric ion gel electrolyte of a high-concentration zinc salt. Background Art
[0002] Zinc-ion batteries use aqueous solution as electrolyte, with a volume energy density of up to 5855 mAh / cm 3 , about 3 times that of lithium-ion batteries, and the abundance of its raw material zinc is about 300 times that of lithium. At the same time, it has the characteristics of safety, environmental protection, and simple preparation process. It is a lithium-ion battery alternative product with great development prospects.
[0003] However, the aqueous electrolyte of zinc-ion batteries is prone to problems such as leakage and zinc dendrite growth during long-term use, and also produces a variety of side reactions caused by aqueous solutions, such as hydrogen evolution reaction (HER) and oxygen evolution reaction (OER).
[0004] At present, in order to solve the above zinc dendrite growth problem, the existing technology optimizes the electrolyte composition, such as introducing high concentration of zinc salt to control the deposition rate of zinc ions and extend the battery life. However, high concentration of additive salt will increase the cost of the electrolyte, increase the viscosity of the electrolyte, and significantly reduce the ion conductivity. For example, the existing patent document CN115458816A discloses an organic electrolyte that can be used for zinc ion batteries. It introduces a high concentration of additives into the electrolyte, which limits the ion migration and the conductivity of the electrolyte is only 6.4mS cm -1 .
[0005] On the other hand, in order to solve the above leakage problem, some existing technologies use hydrogel electrolytes. Studies have found that hydrogel electrolytes can not only solve the leakage problem to a large extent, but also hinder the growth of zinc dendrites and extend the cycle life of zinc ion batteries. However, compared with aqueous electrolytes, the water content of gel electrolytes is greatly reduced, resulting in a significant decrease in ion conductivity, which limits the further promotion and application of this type of zinc ion batteries.
[0006] Therefore, there is an urgent need in the art to obtain an electrolyte for zinc ion batteries that can overcome leakage and zinc dendrite growth, while having few side reactions and relatively high conductivity. Summary of the invention
[0007] In view of the technical problems that need to be solved urgently in the prior art, the present invention provides a high-concentration salt polyzwitterionic gel electrolyte and a zinc ion battery and a preparation method, wherein the electrolyte is a gel-type electrolyte, which can effectively overcome the leakage problem, and at the same time it can significantly inhibit the growth of zinc dendrites and the occurrence of side reactions, and solve the problem of significant decrease in ion conductivity existing in conventional high-concentration salt electrolytes and / or gel electrolytes, thereby obtaining a zinc ion battery with both excellent conductive performance and stability.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing a high-concentration salt polyzwitterionic gel electrolyte comprises the following steps:
[0010] (1) respectively obtaining aqueous solutions of anionic monomers, cationic monomers and acrylamide monomers, and mixing them to obtain a monomer mixed solution;
[0011] (2) adding a high concentration of zinc salt to the monomer mixed solution and performing ultrasonic treatment to obtain a monomer-salt mixed solution;
[0012] (3) adding a free radical polymerization initiator, a crosslinking agent and a catalyst to the monomer-salt mixed solution to obtain a prepolymerization system, and adjusting the pH of the prepolymerization system to 4.5-5.5 to obtain a gel prepolymerization solution;
[0013] (4) heating the gel prepolymer solution to polymerize at 35-45° C. to obtain the high-concentration salt polyzwitterion gel electrolyte;
[0014] Wherein, the anionic monomer is 2-acrylamide-2-methylpropane sulfonic acid and / or sodium p-styrene sulfonate; the cationic monomer is acryloyloxyethyl trimethylammonium chloride and / or methacryloyloxyethyl trimethylammonium chloride; the acrylamide-based monomer is selected from one or more of acrylamide, methacrylamide or N-hydroxymethyl acrylamide, and the concentration of the high-concentration zinc salt is 4-10 mol / L.
[0015] In the conventional technical means in this field, the addition of polymer network type additives and / or higher concentrations of zinc salts usually reduces the activity of water molecules, changes the zinc ion diffusion kinetics, and reduces the growth of zinc dendrites, but also causes the occurrence of electrolyte phase transition, which significantly reduces the ionic conductivity of the electrolyte. The above technical scheme of the present invention can synergize the polyzwitterionic network in the electrolyte with the high concentration salt, and enhance the dissociation of the salt through some special properties of the functional groups on the polyzwitterionic network, such as its high polarity, and become a jump site for ion migration, so as to achieve efficient ion conduction characteristics. Therefore, it can solve the contradiction between suppressing the growth of zinc dendrites and obtaining high ionic conductivity at the same time, and obtain a zinc ion battery with excellent safety performance, service life and electrical performance.
[0016] According to some preferred embodiments of the present invention, the zinc salt is zinc chloride, the initiator is ammonium persulfate and / or potassium persulfate, and the crosslinking agent is N,N'-methylenebisacrylamide and / or ethylene glycol diacrylate.
[0017] According to some preferred embodiments of the present invention, the mass ratio of the anionic monomer, the cationic monomer and the acrylamide monomer is 1-2:4-5:5-6, more preferably 1:4:5.
[0018] The inventors unexpectedly discovered that, under the above ratio, the gel electrolyte has high-density hydrogen bonds and ionic bonds, and the gel electrolyte has excellent mechanical properties.
[0019] According to some preferred embodiments of the present invention, the total mass of the anionic monomer, the cationic monomer and the acrylamide monomer is 10-20 wt % of the mass of the gel prepolymer solution.
[0020] The inventors unexpectedly discovered that under a certain mass ratio, the water content of the gel electrolyte is moderate and the polymerization molding effect is good.
[0021] According to some preferred embodiments of the present invention, the frequency of the ultrasonic treatment is 50-100 Hz, and the time is 10-30 min.
[0022] According to some preferred embodiments of the present invention, obtaining the aqueous solution of the anionic monomer, the cationic monomer and the acrylamide monomer comprises: adding the anionic monomer, the cationic monomer and the acrylamide monomer into deionized water respectively, and obtaining a uniformly dissolved solution by ultrasonic treatment.
[0023] According to some preferred embodiments of the present invention, the temperature of the heating polymerization is 40° C. and the time is 6-12 hours.
[0024] According to some preferred embodiments of the present invention, the pH is adjusted by the content of the catalyst, and the catalyst is N,N,N',N'-tetramethylethylenediamine.
[0025] The inventors unexpectedly discovered that the preferred catalyst can not only effectively catalyze the free radical polymerization reaction, but also simultaneously adjust the pH of the prepolymerization system and extend the cycle life of the battery.
[0026] The present invention further provides a high-concentration salt polyzwitterion gel electrolyte prepared according to the above preparation method.
[0027] The electrolyte contains a three-dimensional network with an amphoteric copolymer formed by polymerization of anionic monomers, cationic monomers and acrylamide-based monomers, and high-concentration salt is evenly distributed in the three-dimensional network, thereby utilizing ionic functional groups in the three-dimensional network as jumping points for ion transmission.
[0028] The present invention further provides a zinc ion battery containing the high-concentration salt polyzwitterion gel electrolyte.
[0029] In some preferred embodiments, the negative electrode material of the zinc ion battery is zinc foil, and the positive electrode material is vanadium pentoxide.
[0030] The present invention has the following beneficial effects:
[0031] (1) The preparation method of the present invention copolymerizes three monomers, namely, anionic monomers, cationic monomers, and acrylamide monomers, to form an amphoteric ternary copolymer network structure, namely, a polyzwitterionic network, wherein the acrylamide structure can participate in the formation of hydrogen bonds to reduce the activity of water molecules. At the same time, the polyzwitterionic network can form a dual ion channel inside the hydrogel, regulate the transmission path of zinc ions, and limit the two-dimensional diffusion of zinc ions, so that zinc ions can be uniformly deposited and stripped on the surface of the zinc negative electrode, effectively inhibiting the growth of zinc dendrites and extending the cycle life of the battery;
[0032] (2) In the electrolyte obtained by the present invention, the polyzwitterionic network and the high-concentration salt solution coexist, which can not only play their respective roles, but also produce a synergistic effect between them. For example, the special properties of the ionic functional groups on the polyzwitterionic network, such as high polarity, help the dissociation of salt in the high-concentration salt solution and increase the ion conductivity. The ionic functional groups also further become the transition sites for zinc ion migration, increasing the ion conduction mode, so that the prepared gel electrolyte exhibits efficient ion conduction characteristics, avoiding the problem of a significant decrease in conductivity that often occurs in simple high-concentration salt electrolytes or polymer network electrolytes;
[0033] (3) In some preferred preparation schemes of the present invention, tetramethylethylenediamine is used to adjust the pH value of the electrolyte. This method is easy to operate and can further extend the cycle life of the battery;
[0034] (4) The electrolyte of the present invention can be prepared by a one-step method with mild reaction conditions, low cost, safety and reliability, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The AC impedance curves of the blocked batteries corresponding to the gel electrolytes prepared in Examples 1-4.
[0036] Figure 2 The symmetric battery with the gel electrolyte prepared in Example 1 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.
[0037] Figure 3The symmetric battery with the gel electrolyte prepared in Example 2 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.
[0038] Figure 4 The symmetric battery with the gel electrolyte prepared in Example 3 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.
[0039] Figure 5 The symmetric battery with the gel electrolyte prepared in Example 4 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.
[0040] Figure 6 The cyclic voltammetry curve of the zinc-vanadium pentoxide full cell with the gel electrolyte prepared in Example 4.
[0041] Figure 7 The symmetric battery with the gel electrolyte prepared in Example 5 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.
[0042] Figure 8 The symmetric battery with the gel electrolyte prepared in Example 6 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.
[0043] Fig. 9 This is the AC impedance curve of the blocked battery prepared in Comparative Example 1.
[0044] Fig.10 The liquid Zn-Zn symmetric battery prepared in Comparative Example 1 is -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density. DETAILED DESCRIPTION
[0045] The technical scheme of the present invention will be further described below in conjunction with the embodiments and drawings of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0046] In the following examples, the ionic conductivity is calculated by measuring the electrochemical impedance spectroscopy (EIS) curve of the blocked battery using an electrochemical workstation.
[0047] Example 1
[0048] Weigh 0.05 g 2-acrylamide-2-methylpropanesulfonic acid (AMPS), 0.2 g DMC (acryloyloxyethyl trimethyl ammonium chloride), and 0.25 g acrylamide (AM) and add them to 1.5 mL pure water. Place them in an ultrasonic cleaner and ultrasonicate for 10 min to dissolve the monomers. Add 0.816 g ZnCl 2 , and 4 M ZnCl was obtained by ultrasonic treatment for 20 min. 2 The monomer solution was then added with 6 mg of ammonium persulfate, 20 μL of N,N,N',N'-tetramethylethylenediamine and 1 mg of N,N'-methylenebisacrylamide and ZnCl 2 The monomer solutions are mixed evenly to obtain a prepolymer solution;
[0049] The prepolymer solution was transferred to a glass mold, placed in an oven, and subjected to free radical polymerization reaction at 40° C. for 6 h to obtain a high-concentration salt-polyzwitterionic gel electrolyte.
[0050] Furthermore, the gel electrolyte prepared in this embodiment was assembled with two stainless steel sheets into a stainless steel sheet blocking cell, and an electrochemical AC impedance test was performed. The test results are as follows: Figure 1 As shown in Figure 2, the ionic conductivity of the gel electrolyte obtained in this example is 17.91 mS cm -1 .
[0051] The gel electrolyte prepared in this example was assembled into a Zn-Zn symmetrical battery and subjected to an electrochemical cycle stability performance test. The test results are shown in FIG. Figure 2 As shown, it can be seen that at 1 mA cm -2 The current density and 1 mAh cm -2 At a capacity density of , the symmetrical battery can cycle stably for 510 hours, indicating that the gel electrolyte on its surface effectively inhibits the growth of zinc dendrites and has good cycle stability.
[0052] Example 2
[0053] Weigh 0.05g AMPS, 0.2g DMC, and 0.25g AM, add them into 1.5mL pure water, put them into an ultrasonic cleaner and ultrasonicate for 10min to dissolve the monomers. Add 1.224g ZnCl 2 6 M ZnCl was obtained by ultrasonic treatment for 20 min. 2The monomer solution was then added with 6 mg of ammonium persulfate initiator, 20 μL of N,N,N',N'-tetramethylethylenediamine and 1 mg of N,N'-methylenebisacrylamide and ZnCl 2 The monomer solutions are mixed evenly to obtain a prepolymer solution;
[0054] The prepolymer solution was transferred into a glass mold and placed in an oven to undergo free radical polymerization at 40° C. for 6 h to obtain a high-concentration salt-polyzwitterionic gel electrolyte.
[0055] The high-concentration salt polyzwitterion gel electrolyte prepared in this example was assembled with two stainless steel sheets into a stainless steel sheet blocking cell, and an electrochemical AC impedance test was performed. The test results are as follows: Figure 1 As shown in Figure 2, the ionic conductivity of the gel electrolyte obtained in this example is found to be 21.53 mS cm -1 .
[0056] The high-concentration salt polyzwitterion gel electrolyte prepared in this example was assembled into a Zn-Zn symmetric battery and subjected to an electrochemical cycle stability performance test. The test results are shown in FIG. Figure 3 As shown, it can be seen that at 1mA cm -2 The current density and 1 mAh cm -2 At a capacity density of , the symmetrical battery can be cycled stably for 890 hours.
[0057] Example 3
[0058] Weigh 0.05g AMPS, 0.2g DMC, and 0.25g AM, add them into 1.5mL pure water, and place them in an ultrasonic cleaner for 10 minutes to dissolve the monomers. Add 2.04g ZnCl 2 10 M ZnCl was obtained by ultrasonic treatment for 20 min. 2 Then add 6mg ammonium persulfate initiator, 20μL N,N,N',N'-tetramethylethylenediamine and 1mg N,N'-methylenebisacrylamide and ZnCl 2 The monomer solutions are mixed evenly to obtain a prepolymer solution;
[0059] The prepolymer solution was transferred into a glass mold and placed in an oven to undergo free radical polymerization at 40° C. for 6 h to obtain a high-concentration salt-polyzwitterionic gel electrolyte.
[0060] The high-concentration salt polyzwitterion gel electrolyte prepared in this example was assembled with two stainless steel sheets into a stainless steel sheet blocking cell, and an electrochemical AC impedance test was performed. The test results are as follows: Figure 1 As shown in Figure 2, the ionic conductivity of the gel electrolyte obtained in this example is found to be 23.41 mS cm -1 .
[0061] The high-concentration salt polyzwitterion gel electrolyte prepared in this example was assembled into a Zn-Zn symmetric battery and subjected to an electrochemical cycle stability performance test. The test results are shown in FIG. Figure 4 As shown, it can be seen that at 1mA cm -2 The current density and 1 mAh cm -2 At a capacity density of , the symmetrical battery can be cycled stably for 1500 hours.
[0062] Example 4
[0063] Weigh 0.05g AMPS, 0.2g DMC, and 0.25g AM, add them into 1.5mL pure water, and place them in an ultrasonic cleaner for 10 minutes to dissolve the monomers. Add 1.632g ZnCl 2 8 M ZnCl was obtained by ultrasonic treatment for 20 min. 2 Then add 6mg ammonium persulfate initiator, 20μL N,N,N',N'-tetramethylethylenediamine and 1mg N,N'-methylenebisacrylamide and ZnCl 2 The monomer solutions are mixed evenly to obtain a prepolymer solution;
[0064] The prepolymer solution was transferred into a glass mold and placed in an oven to undergo free radical polymerization at 40° C. for 6 h to obtain a high-concentration salt-polyzwitterionic gel electrolyte.
[0065] The high-concentration salt polyzwitterion gel electrolyte prepared in this example was assembled with two stainless steel sheets into a stainless steel sheet blocking cell, and an electrochemical AC impedance test was performed. The test results are as follows: Figure 1 As shown in Figure 2, the ionic conductivity of the gel electrolyte obtained in this example is found to be 43.99 mS cm -1 .
[0066] The high-concentration salt polyzwitterion gel electrolyte prepared in this example was assembled into a Zn-Zn symmetric battery and subjected to an electrochemical cycle stability performance test. The test results are shown in FIG. Figure 5 As shown, it can be seen that at 1mA cm -2 The current density and 1 mAh cm -2 At a capacity density of , the symmetrical battery can be cycled stably for 2000 hours.
[0067] Furthermore, the high-concentration salt polyzwitterionic gel electrolyte prepared in this example was assembled into a zinc-vanadium pentoxide full battery and subjected to a cyclic voltammetry performance test, with the parameters set at 0.4 V to 1.4 V and a scan rate of 1 mV s -1 , the test results are as follows Figure 6As shown, it can be seen that the positions of the reduction peaks are mainly located near 0.64 V, and the position of the oxidation peak is located near 1.09 V. The curves are highly symmetrical, indicating that zinc ions can achieve reversible deposition and dissolution reactions in this high-concentration salt polyzwitterionic gel electrolyte.
[0068] Example 5
[0069] Weigh 0.05g AMPS, 0.2g DMC, and 0.25g AM, add them into 1.5mL pure water, and place them in an ultrasonic cleaner for 10 minutes to dissolve the monomers. Add 1.632g ZnCl 2 8 M ZnCl was obtained by ultrasonic treatment for 20 min. 2 Then add 6mg ammonium persulfate initiator, 10μL N,N,N',N'-tetramethylethylenediamine (pH of prepolymer solution is less than 3) and 1mg N,N'-methylenebisacrylamide and ZnCl 2 The monomer solutions are mixed evenly to obtain a prepolymer solution;
[0070] The prepolymer solution was transferred into a glass mold and placed in an oven to undergo free radical polymerization at 40° C. for 6 h to obtain a high-concentration salt-polyzwitterionic gel electrolyte.
[0071] The high-concentration salt polyzwitterion gel electrolyte prepared in this example was assembled into a Zn-Zn symmetric battery and subjected to an electrochemical cycle stability performance test. The test results are shown in FIG. Figure 7 As shown, it can be seen that at 1 mA cm -2 The current density is 1 mAh cm -2 At a capacity density of , the symmetrical battery can cycle stably for 310 hours.
[0072] It can be seen that after reducing the content of N,N,N',N'-tetramethylethylenediamine, the stability of the symmetric battery decreased and the growth of zinc dendrites was promoted.
[0073] Example 6
[0074] Weigh 0.05g AMPS, 0.2g DMC, and 0.25g AM, add them into 1.5mL pure water, and place them in an ultrasonic cleaner for 10 minutes to dissolve the monomers. Add 1.632g ZnCl 2 8 M ZnCl was obtained by ultrasonic treatment for 20 min. 2 Then add 6mg ammonium persulfate initiator, 60μL N,N,N',N'-tetramethylethylenediamine (prepolymer solution pH greater than 7) and 1mg N,N'-methylenebisacrylamide and ZnCl 2 The monomer solutions are mixed evenly to obtain a prepolymer solution;
[0075] The prepolymer solution was transferred into a glass mold and placed in an oven to undergo free radical polymerization at 40° C. for 6 hours to obtain the high-concentration salt polyzwitterionic gel electrolyte.
[0076] The high-concentration salt polyzwitterion gel electrolyte prepared in this example was assembled into a Zn-Zn symmetric battery and subjected to an electrochemical cycle stability performance test. The test results are shown in FIG. Figure 8 As shown, it can be seen that at 1 mA cm -2 The current density and 1 mAh cm -2 At a capacity density of 1.5 Ω, the symmetrical battery can cycle stably for 360 hours.
[0077] It can be found that after increasing the content of N,N,N',N'-tetramethylethylenediamine, the stability of the symmetrical battery decreases, the side reactions increase, the surface flatness of the electrode material decreases after being covered by the by-products, and the growth of zinc dendrites is also promoted.
[0078] Comparative Example 1
[0079] Zinc chloride was dissolved in deionized water to prepare a 2M zinc chloride solution. The 2M zinc chloride was used as the liquid electrolyte of the aqueous zinc ion battery. Conventional glass fiber was used as a separator to assemble a stainless steel sheet aqueous blocking battery. The AC impedance curve is shown in Fig. 9 As shown in Figure 2, the calculated ionic conductivity of the aqueous electrolyte is 12.51 mS cm -1 .
[0080] The aqueous electrolyte was assembled into a liquid Zn-Zn symmetric battery for electrochemical cycle stability performance testing. The test results are as follows Fig.10 As shown, it can be seen that at 1 mA cm -2 The current density and 1 mAh cm -2 At a capacity density of , the symmetrical battery can cycle stably for 45 hours. After 45 hours, the battery loses stability due to the growth of zinc dendrites and side reactions.
[0081] It can be seen from the above comparative examples that the ionic conductivity of the gel electrolytes obtained in Examples 1 to 6 of the present invention is significantly improved, and the service life of the corresponding zinc ion batteries is significantly improved.
[0082] It should be noted that the above is only a preferred embodiment of the present invention, which should not limit the protection scope of the technical solution of the present invention. Any modification of the technical solution recorded in the above embodiments and equivalent replacement of technical features by ordinary technicians in the field within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-concentration salt polyzwitterionic gel electrolyte, characterized in that: It includes the following steps: (1) respectively obtaining aqueous solutions of anionic monomers, cationic monomers and acrylamide monomers, and mixing them to obtain a monomer mixed solution; (2) adding a high concentration of zinc salt to the monomer mixed solution and performing ultrasonic treatment to obtain a monomer-salt mixed solution; (3) adding a free radical polymerization initiator, a crosslinking agent and a catalyst to the monomer-salt mixed solution to obtain a prepolymerization system, and adjusting the pH of the prepolymerization system to 4.5-5.5 to obtain a gel prepolymerization solution; (4) heating the gel prepolymer solution to polymerize at 35-45° C. to obtain the high-concentration salt polyzwitterion gel electrolyte; Wherein, the anionic monomer is 2-acrylamide-2-methylpropane sulfonic acid and / or sodium p-styrene sulfonate; the cationic monomer is acryloyloxyethyl trimethylammonium chloride and / or methacryloyloxyethyl trimethylammonium chloride; the acrylamide-based monomer is selected from one or more of acrylamide, methacrylamide or N-hydroxymethyl acrylamide, and the concentration of the high-concentration zinc salt is 4-10 mol / L.
2. The preparation method according to claim 1, characterized in that: in, The zinc salt is zinc chloride, the initiator is ammonium persulfate and / or potassium persulfate, and the crosslinking agent is N,N'-methylenebisacrylamide and / or ethylene glycol diacrylate.
3. The preparation method according to claim 1, characterized in that: in, The mass ratio of the anionic monomer, the cationic monomer and the acrylamide monomer is 1-2:4-5:5-6; and / or the total mass of the anionic monomer, the cationic monomer and the acrylamide monomer is 10-20wt% of the mass of the gel prepolymer solution.
4. The preparation method according to claim 1, characterized in that: in, The frequency of the ultrasonic treatment is 50-100 Hz, and the time is 10-30 min.
5. The preparation method according to claim 1, characterized in that: The aqueous solution of the anionic monomer, the cationic monomer and the acrylamide monomer is obtained by respectively adding the anionic monomer, the cationic monomer and the acrylamide monomer into deionized water and obtaining a uniformly dissolved solution through ultrasonic treatment.
6. The preparation method according to claim 1, characterized in that: The temperature of the heating polymerization is 40° C. and the time is 6-12 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The pH is adjusted by the content of the catalyst, and the catalyst is N,N,N',N'-tetramethylethylenediamine.
8. The high-concentration salt polyzwitterion gel electrolyte prepared by the preparation method according to any one of claims 1 to 7.
9. A zinc ion battery comprising the high-concentration salt polyzwitterionic gel electrolyte according to claim 8.
10. The zinc ion battery according to claim 9, characterized in that: The negative electrode material is zinc foil and the positive electrode material is vanadium pentoxide.
Citation Information
Patent Citations
Organic electrolyte, zinc ion battery and preparation method of zinc ion battery
CN115458816A
Polymer rechargeable zinc ion battery
CN102683756A
Method for in-situ preparation of solid electrolyte based on local high-concentration precursor solution
CN114361603A
Dual-network self-healing hydrogel electrolyte, preparation method thereof and aqueous zinc ion battery
CN117362523A
Polymer solid electrolyte
JP2004281147A
Cited By
Diaphragm, preparation method thereof and secondary battery
CN121149594A
Polyzwitterionic hydrogel electrolyte as well as preparation method and application thereof
CN121306813A
A polyzwitterionic hydrogel electrolyte, and a preparation method and application thereof
CN121306813B